Autor filmowy według przepisów prawa w systemach droit d`auteur i copyright. Zarys problematyki - Racięski, Bolesław (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2013)
The aim of the article is to outline the key issues surrounding legal notions of film authorship. For scholars interested in studying the process of production it is extremely important to analyze the status and scope of power of its participants as well as their position in the hierarchy – one of the main sources of priveleges is the fact of being recognized by the law as the author of the work produced. The article depicts the benefits of such situation, but its main aim is to descibe the legal rules of granting the status of the author. Outlined are the issues emerged from the two radically different legal system – european droit d`auteur tradition and american copyright. The first one honours the artists while the other focuses mostly on providing the certainty of the economics, so the actual authors of the work are not that important. The paper points to the fact that – especially in the case of american copyright – the actual (determined by law) situation of a creator may differ significantly from the character of their contribution to the process of producing a film. Analysis of the rules and principles of the law is essential to the understanding of the structural determinants of film production and deserves no less attention than social, political and economic factors.

Celem artykułu jest zarysowanie podstawowych zagadnień prawnej problematyki autorstwa filmowego. Dla badaczy procesu produkcji filmowej niezwykle ważna jest analiza statusu i zakresu możliwości jego uczestników oraz ich pozycja w hierarchii – jednym z podstawowych źródeł przywilejów jest z kolei fakt zostania uznanym przez prawo za autora produkowanego utworu. Artykuł tłumaczy, jakie korzyści niesie ze sobą taka sytuacja, przede wszystkim jednak opisuje prawne mechanizmy przyznawania statusu „autora”. Zarysowane zostały regulacje powstałe na gruncie dwóch radykalnie odmiennych od siebie systemów – europejskiego droit d`auteur oraz amerykańskiego copyright. Pierwszy z nich w centrum stawia twórców, drugi skupia się na zapewnieniu pewności obrotu gospodarczego, przez co faktyczni autorzy zepchnięci zostają na margines (za autora uznane być może nawet studio filmowe). Artykuł zwraca uwagę na fakt, iż – zwłaszcza w przypadku copyright - rzeczywista (określana przez prawo) sytuacja twórcy może znacznie odbiegać od charakteru jego zaangażowania w powstawanie filmu. Analiza przepisów i zasad prawa jest kluczowa dla zrozumienia strukturalnych uwarunkowań działalności przemysłów filmowych i należy poświęcać jej nie mniej uwagi niż czynnikom natury społecznej, politycznej i ekonomicznej.
Film author according to law in droit d`auteur system and copyright system
Keywords: film author; copyright; droit d`auteur; film production; autor filmowy; produkcja filmowa; prawo autorskie